FEM-based practical recommendations for detailing UHPC wet joints of precast slabs - Silva, Marcos Antonio do Rosario da; Sousa, Alex Micael Dantas de [UNESP]; Araújo, Daniel de Lima; Sanabria Díaz, Rafael Andrés; Krahl, Pablo Augusto; El Debs, Mounir Khalil (Elsevier, 2025)
The structural performance of bridges with full-depth precast slabs relies on the effectiveness of cast-in-place concrete wet joint in transferring forces. These wet joints are formed over interlocking reinforcement bars, with wet joint detailing being a critical factor in the behavior of slab connections. The reinforcement arrangement should be simple to manufacture, easy to assemble on-site, and ensure the durability and strength of the connection, which can be optimized by using ultra-high-performance fiber-reinforced concrete (UHPC). This study investigates the performance of different reinforcement wet joint configurations in connections between full-depth precast slabs and evaluates their performance using UHPC as wet joint filler material. Experimental results were selected from the literature to calibrate the behavior of finite element model of the wet joint. Numerical results showed that the UHPC properties contribute significantly to enhance connection performance, particularly in the anchorage between reinforcement bars, allowing for reduced reinforcement splice length compared to conventional concrete. Anchorage failure is avoided with a minimum connection length of 200 mm and a splice length of at least 7.5 times the diameter of the longitudinal bars (db). Additionally, the use of headed or looped bars in the connection improves reinforcement anchorage.
Recomendações práticas baseadas em elementos finitos para detalhamento de juntas úmidas de concreto de ultra-alto desempenho em lajes pré-moldadas
Keywords: Full-depth precast slab; Connection; UHPC; Numerical simulation; Reinforcement joints